Program Dana Pemberdayaan Ekonomi Masyarakat Di Kecamatan Oebobo Kota Kupang - Semarch Dewi Ayu Putri Bida; Nikson Tameno; Novi Theresia Kiak (BALANCE: Economic, Business, Management and Accounting Journal, 2021)
This study examines the Community Economic Empowerment Fund Program, one of the policies to empower people in Kupang City with interest-free funds as capital for developing productive businesses to increase the potential economic community. This study aims to explain the impact of community business development on community empowerment programs by looking at the factors in the delay in returning the program funds and using qualitative descriptive analysis techniques with investigations by interviewing several key informants, including the Chairperson of the LPM, village facilitators, and community recipients of PEM funds. The results showed the implementation of the Community Economic Empowerment Fund program in Oebobo District had a positive impact on increasing community income, community business productivity, community independence, the initial funding roll-out stage from 2013 to 2019 for the community in Oebobo District, Kupang City, and also increasing public awareness of community economic empowerment fund assistance that helps develop community businesses. But on the other hand, there are still arrears caused by several factors, namely lack of understanding from the recipient of the funds, business congestion, absence of financial reports, culture, change of facilitators, and other unexpected things. Keywords                    : Community independence; Increased revenue; PEM Fund ProgramCorrespondence to      : novi.kiak@staf.undana.ac.id                                                 Penelitian ini mengkaji Program Dana Pemberdayaan Ekonomi Masyarakat yang merupakan salah satu kebijakan untuk memberdayaan masyarakat di Kota Kupang dengan  bantuan dana tanpa bunga sebagai modal untuk pengembangan usaha produktif demi meningkatkan potensi perekonomian masyarakat. Penelitian ini bertujuan untuk menjelaskan dampak pengembangan usaha masyarakat dengan adanya program pemberdayaan masyarakat dengan melihat faktor- faktor  terjadinya keterlambatan  pengembalian dana program tersebut. Dengan menggunakkan teknik analisis deskriptip kualitatif dengan investigasi mewawancarai beberapa informan kunci, meliputi Ketua LPM, fasilitator kelurahan selaku tenaga pendamping serta masyarakat penerima dana PEM. Hasil penelitian menunjukkan bahwa Pelaksanaan program Dana Pemberdayaan Ekonomi Masyarakat di Kecamatan Oebobo menghasilkan dampak positif meningkatkan pendapatan masyarakat, produktivitas usaha masyarakat, kemandirian masyarakat, tahap pengguliran dana tahap awal  dari tahun 2013 hingga 2019 bagi masyarakat di Kecamatan Oebobo Kota Kupang dan juga peningkatan kesadaran masyarakat terhadap bantuan dana pemberdayaan ekonomi masyarakat yang membantu pengembangan usaha masyarakat. Namun disisi lain masih terdapat tunggakan  yang disebabkan oleh beberapa faktor yaitu kurang ada pemahaman dari penerima dana , kemacetan usaha, tidak adanya  laporan keuangan , budaya, pergantian fasilitator dan hal tak terduga lainnya. Kata Kunci:  Kemandirian masyarakat; Peningkatan Pendapatan; Program Dana PEM